MODE KEGAGALAN STRUKTUR PIPA PADA CANTILEVER TUNGGAL - -, Darwinto; Saleh, Agus; Ginting, Edison; Damayanti, Eva; Simorangkir, Rudi M (Jurnal TEDC; Vol 19 No 2 (2025): JURNAL TEDC, 2025)
The Cantilever structure is a structure that is commonly found in general. This structure usually consists of a beam that is supported or fixed at one end, while the other end of the material used as a Cantilever beam works openly (without support) and has a specific load at its end. When a load is applied to the open side, the supported end will experience a moment that varies in value depending on the applied load. This type of structure is widely used, generally in the installation of CCTV in open areas and in street lighting. Based on this background, the author aims to conduct research related to the planned material strength, namely carbon pipes. In addition, the research is conducted to minimize excessive expenditures, meaning that the goal is to design something that is useful, affordable, and has good durability or resilience in its operation. In this study, the method used is data collection through literature studies, interviews, or direct observations of the positions of the poles that have been installed along the passed roads. The result of this research is a robust yet inexpensive single cantilever structure, thus it can be concluded that a good, strong, and load-resistant structure does not always have to be made at a high cost.